Cultural and Creative Industries Worldwide and in Russia - Vladimir MATVEEV; Olga RUDAKOVA; Alla ANNENKOVA; Anna MIKHAYLINA (Communications of International Proceedings, 2021)
Nowadays, there is a growing awareness both in academic and political circles of the contribution of the cultural sphere to the socio-economic development of countries . Theorists and practitioners analyse the role of culture as a factor behind an economic growth through the  prism of creative industries.  Cultural and creative industries constitute an economic sector in which a significant part of the added value is generated through creative activities and management of intellectual property rights. The last decade have seen positive dynamics in the cultural and creative industries, namely greater contribution of the industries to GDP, growing employment of the economically active population in this area, record figures of creative goods and services sold in the world market. According to the HSE ISSEK digest, in 2019, the creative industries generated 3% of global GDP and provided jobs for 1% of the economically active population of the planet. In 2019, China and the United States were the global leaders in terms of the share and volume of GDP generated by cultural and creative industries. The gross value added, generated in these industries, represented 4.2% of GDP in China and  4.3% of GDP in the United States. In Russia, in 2019, the gross value added generated by cultural and creative industries accounted for 2.4% of GDP, which is close to the global average, but significantly lower than in the leading countries. In Italy, the UK and Australia, the share of creative industries in GDP was 6.1%, 5.8% and 5.7% of GDP respectively.
Keywords: Creative Industries; Culture; Exports Of Creative Goods; Imports Of Creative Goods.